The sound of silence : indigenous perspectives on the historical archaeology of colonialism - Äikäs, Tiina; Salmi, Anna-Kaisa (Berghahn, 2019)
"Colonial encounters between indigenous peoples and European state powers are overarching themes in the historical archaeology of the modern era, and postcolonial historical archaeology has repeatedly emphasized the complex two-way nature of colonial encounters. The volume examines common trajectories in indigenous colonial histories, and explores new ways to understand cultural contact, hybridization and power relations between indigenous peoples and colonial powers from the indigenous point of view. By bringing together a wide geographical range and combining multiple sources such as oral histories, historical record, and contemporary discourses with archaeological data, the volume finds new multivocal interpretations of colonial histories"--